2015
DOI: 10.3899/jrheum.150515
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Measures in Polymyalgia Rheumatica. A Systematic Review

Abstract: Objective.To identify the instruments used to assess polymyalgia rheumatica (PMR) in published studies.Methods.A systematic literature review of clinical trials and longitudinal observational studies related to PMR, published from 1970 to 2014, was carried out. All outcome and assessment instruments were extracted and categorized according to core areas and domains, as defined by the OMERACT (Outcome Measures in Rheumatology) Filter 2.0.Results.Thirty-five articles (3221 patients) were included: 12 randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…We now need to establish 'how' to best measure these domains. A previous systematic review (Duarte et al, 2015) found a wide range of instruments had been used but was limited in its search strategy and inclusion criteria and did not assess the quality of the evidence found. Furthermore, no review of the evidence for measurement properties of instruments in PMR has been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…We now need to establish 'how' to best measure these domains. A previous systematic review (Duarte et al, 2015) found a wide range of instruments had been used but was limited in its search strategy and inclusion criteria and did not assess the quality of the evidence found. Furthermore, no review of the evidence for measurement properties of instruments in PMR has been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review of outcome measures used in PMR research studies [3] identified a wide variety of instruments in use, none of which were specifically developed to measure symptom burden in patients with PMR. Less than 10% of studies measured physical function, quality of life or fatigue, despite these being important to patients [4].…”
Section: Introductionmentioning
confidence: 99%
“…This first set was completed by identification of missing items by reviewing the literature, resulting in addition of 6 further items required for calculation of the Charlson Comorbidity Index 31. Existing work on data collection in PMR and RA15–20 revealed another six parameters, namely ethnicity, fatigue, functional capacity, quality of life, morning stiffness and cumulative GC dose. No instruments relating to GCA were found in the EULAR Outcome Measures Library 32.…”
Section: Resultsmentioning
confidence: 99%
“…Search terms included ‘vasculitis’, ‘giant cell arteritis’, ‘polymyalgia rheumatica’ accompanied by ‘outcome measures’, ‘registry’, ‘core data set’, ‘reporting’ and ‘epidemiology’. Potentially relevant domains and items were identified by scanning-related work done in polymyalgia rheumatica (PMR)15–18 and RA 19 20. The compilation of items was also counterchecked with current guidelines on the management of GCA1 21 as well as EULAR, European Vasculitis Society (EUVAS) and European Union Committee of Experts on Rare Diseases (EUCERD) recommendations on data collection and patient registries 22–26.…”
Section: Methodsmentioning
confidence: 99%